Fatal typhoid intestinal perforation in post tubal ligation death with an alleged medical negligence: a rare case report - Ghormade, Pankaj Suresh; Keoliya, Ajay Narmadaprasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Worldwide tubal sterilization is commonly used procedure for family planning method. Tubal ligation by minilaparotomy under local anaesthesia is most commonly used method of female sterilization in India. The death rate after tubal sterilizations is 72/100000 for all procedures and mainly due to general anaesthesia or vascular injuries. Iatrogenic injury to bowel can occur in minilaparotomy tubal ligations if there are dense adhesions of intestines or history of previous surgery. In the present case of interval post tubal ligation by minilaparotomy, fatal ileal perforation due to typhoid fever was detected on autopsy which was confirmed after complete histological and lab investigations. Atypical complications of typhoid fever were also noted. In developing countries, typhoid fever is the leading cause of non-traumatic free perforation of intestine and its incidence ranges from 0.9% to 39%, with a high mortality rate. This is rare case of an alleged medical negligence after surgery; in which deciding factor was cause of intestinal perforation i.e. iatrogenic or natural and it posed a difficult challenge.